Wpływ technologii informacyjno-komunikacyjnych na funkcjonowanie przedsiębiorstw - Pohulak-Żołędowska, Elżbieta (The Influence of ICT on Functioning of Enterprices, 2008)
The increased use of Information and Communication Technology has had a radical impact on the way we live - nowhere more so on our enterprises. We now talk of a „new economy", encompassing all different ways that the new technology affects how we earn and spend money and organize business. The goal of this article is to show the ability of enterprises to adopt new conditions and also to show the mainstream of the change.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 43-52